Kebugaran Jasmani melalui Permainan Tradisional sebagai Jati Diri Bangsa - Sumantri, Riyan Jaya; Azizah, Alfiah Rizqi; Syarif, Ahmad; Irawan, Yogi Ferdy; Widodo, Puput; Parmadi, Mokhamad; Burhaein, Erick; Santoso, Rahmawan; Wijaya, Febri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
In the 90s, traditional games such as gobak gobrak sodor, engklek, jump rope, panggal (spinning wheel), egrang and patok lele turned into the main games played by children after school or during school holidays. However, due to the development of the times, the influence of the development of technology and social media has changed the games of today's children from group and active to individual and passive. Traditional games that are full of culture, national values, and even elements that are useful for child development are being neglected. The high level of children's addiction to gadgets affects habits and behavior. This dedication raises the importance of preserving traditional games in the modern era as it is today. Traditional games have many benefits, apart from being the nation's cultural heritage, traditional games can also act as a tool to train children's motor development, children's social interaction skills, and also character building in children. Preserving national culture in the form of traditional games to shift children's dependence on gadgets through physical education. Restoring traditional games to be one of the main games played by children to create a cultured generation and superior character. The implementation method used is socialization and direct practice in the field. Traditional games have several elements of strength, endurance, flexibility, agility, coordination, balance, and reaction speed. Application to students can increase the degree of physical fitness in students and provide a role for the preservation of traditional games for students.